Beban Kognitif Intrinsik Siswa Kepribadian Guardian dalam Memecahkan Masalah Matematika Ditinjau dari Gaya Belajar - Falah, Bintari Nur; Wijayanti, Pradnyo; Masriyah, Masriyah (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2022)
The intrinsic cognitive load of each student is different in solving math problems. This study aims to describe the intrinsic cognitive load of students with guardian personality in solving math problems at SMK PGRI 1 Tulungagung with learning styles. This research uses qualitative research with a case study approach. Collecting data using tests, questionnaires to classify personality types and learning styles, and interviews. Tests and questionnaires were carried out in class XI, then 6 research subjects were selected to represent the guardian personality with visual, kinesthetic, and auditory learning styles. Data analysis techniques are carried out through the data reduction stage, data presentation, and drawing conclusions. The results showed that the thinking process of guardian personality students with learning styles was: (1) visual. Students do not know what concepts are used to solve the questions, students do not know the formulas used to solve the questions, and students cannot solve the questions until the end correctly because they do not know how to do them; (2) kinesthetic. Students do not know what concepts are used to solve the questions and students know the formulas used to solve the questions, and students cannot solve the questions until the end correctly because students do not understand correctly what is being asked in the problem; (3) auditory. Students understand what is known and asked about the problem so that they are able to solve the problem correctly.